COX‐2/PGE2 axis regulates hippocampal BDNF/TrkB signaling via EP2 receptor after prolonged seizures. Issue 3 (9th June 2020) - Yu, Ying; Jiang, Jianxiong
Abstract: Objective: The objective of this study was to identify the signaling pathway that is immediately triggered by status epilepticus (SE) and in turn contributes to the excessive brain‐derived neurotrophic factor (BDNF)/tropomyosin‐related kinase receptor B (TrkB) signaling within the hippocampus. Methods: We used quantitative PCR, enzyme‐linked immunosorbent assay, and Western blot analysis to examine gene expression at both mRNA and protein levels in the hippocampus following prolonged SE in mice and rats. Three classical animal models of SE were utilized in the present study to avoid any model‐ or species‐specific findings. Results: We showed that both cyclooxygenase‐2 (COX‐2) and BDNF in the hippocampus were rapidly upregulated after SE onset; however, the induction of COX‐2 temporally preceded that of BDNF. Blocking COX‐2 activity by selective inhibitor SC‐58125 prevented BDNF elevation in the hippocampus following SE; prostaglandin E2 (PGE2 ), a major product of COX‐2 in the brain, was sufficient to stimulate hippocampal cells to secrete BDNF, suggesting that a PGE2 signaling pathway might be directly involved in hippocampal BDNF production. Inhibiting the Gαs ‐coupled PGE2 receptor EP2 by our recently developed selective antagonist TG6‐10‐1 decreased the SE‐triggered phosphorylation of the cAMP response element‐binding protein (CREB) and activation of the BDNF/TrkB signaling in the hippocampus. Significance: The molecular mechanisms whereby BDNF/TrkB signaling is upregulated in the hippocampus by SE largely remain unknown. Our findings suggest that COX‐2 via the PGE2 /EP2 pathway regulates hippocampal BDNF/TrkB activity following prolonged seizures. EP2 inhibition by our bioavailable and brain‐permeable antagonists such as TG6‐10‐1 might therefore provide a novel strategy to suppress the abnormal TrkB activity, an event that can sufficiently trigger pathogenic processes within the brain including acquired epileptogenesis.